Dilution-Induced Self-Assembly of Porphyrin Aggregates: A Consequence of Coupled Equilibria - Helmich, Floris; Lee, Cameron C; Nieuwenhuizen, Marko M.L; Gielen, Jeroen C; Christianen, Peter C.M; Larsen, Antje; Fytas, George; Leclère, Philippe E.L.G; Schenning, Albertus P.H.J; Meijer, E.W (Angewandte Chemie (International ed.), 2010)
Piggy‐back porphyrins: The presence of a Lewis base remarkably affects the cooperative self‐assembly of zinc porphyrins. Driven by the susceptibility of the monomer towards the axial ligand, monomer scavenging caused depolymerization of porphyrin aggregates, and dilution caused aggregation by a re‐entrant phase transition. Model predictions were validated by dilution experiments.